Band gap opening of graphene by forming a graphene/PtSe2 van der Waals heterojunction. Issue 72 (22nd September 2017) - Guan, Zhaoyong; Ni, Shuang; Hu, Shuanglin
Abstract : As a promising high performance FET, the graphene/PtSe2 vdW heterojunction has a band gap of 0.264 eV. Abstract : Opening a band gap and finding a suitable substrate for graphene are two challenges for constructing graphene based nano-electronic devices. Recently, a new two-dimensional layered crystal PtSe2 with novel electronic properties has been efficiently synthesized by direct "selenization". In this work, we demonstrate that PtSe2 can be used as a suitable substrate for graphene by forming a graphene/PtSe2 van der Waals (vdW) heterojunction. Hybrid density functional calculations show that PtSe2 as a substrate could introduce a sizeable gap of 0.264 eV into graphene, which is sufficiently large enough for overcoming the thermal excitation of electrons at room temperature. The underlying mechanism for the band gap opening of graphene is that the PtSe2 substrate can produce inhomogeneous electrostatic potential to break the symmetry of the A and B sub-lattices of graphene. By applying a vertical strain to the graphene/PtSe2 vdW heterojunction, the electronic properties of the heterojunction can be effectively tuned. As the vertical strain increases, the band gap monotonously increases and can reach as large as 0.781 eV. The tunable band gap, together with the high carrier mobility of both graphene and PtSe2, suggests the great potential of the PtSe2 /graphene heterojunction in high performance field effect transistors.